Negative online reviews and consumer purchase intentions for search and credence goods: Reactions from users of online shopping platforms in Nigeria - Dudutari, Bereprebofa; Ifeanyi, Aloamaka Judith; Francis, Ndudi (International research journal of management, IT and social sciences, 2022)
This study examined the relationship between negative online reviews and consumer purchase intention. For this study, we used product-brand-related negative online reviews, dealers-related negative online reviews and platform-related online reviews, while the purchase intention of online shoppers was used to proxy consumers’ purchase intention. Negative online reviews were considered in the areas of accessibility, reliability, genuineness, integrity, lead time, user-friendliness, security and satisfaction. To achieve the objectives of the study, a sample of 200 users of online shopping platforms spread across three major cities namely Asaba, Warri and Sapele in Delta State, Nigeria was drawn using the convenience sampling technique. Data were analyzed using the multiple regression estimation techniques. The results of the study indicate that negative online reviews have an inverse and significant relationship with consumer purchase intention. Specifically, product/brand-related negative online reviews, dealers-related negative online reviews and platform-related negative online reviews significantly discourage consumers’ purchase intention. This study, therefore, recommends that negative reviews should be reduced by organizations managing online shopping platforms.